Effects of Extended Grape Ripening With or Without Must and Wine Alcohol Manipulations on Cabernet Sauvignon Wine Sensory Characteristics - Heymann, H.; LiCalzi, M.; Conversano, M.R.; Bauer, A.; Skogerson, K.; Matthews, M. (South African Journal of Enology and Viticulture, 2016)
This study attempts to clarify the consequences for wine flavour that result from harvesting fruit at different maturities. The grapes were harvested from a single vineyard in Paso Robles, and the samples spanned maturity levels from what would be considered early harvest (about 21 °Brix) to late harvest (about 30 °Brix). The wines made from these grapes were analysed using descriptive analysis to investigate the relationships between fruit maturity and wine sensory attributes. In addition, musts and/or wines were chaptalised and/or fortified or watered back to determine the effect of these manipulations on wine sensory properties. This research showed that the sensory attributes of wines made from grapes at different stages of maturation, from about 20 to 30 °Brix, varied in a systematic fashion. Specifically, the wines made from the grapes with a lower Brix were more sour and had more fresh vegetative flavours, while the wines made from the fruit with a high Brix were more hot and bitter and in some cases had more dark fruit flavours and sweetness. Fortifying wines made from lower Brix musts changed the perceptions of the wine sensory profiles more than chaptalising the musts. On the other hand, adding water to higher °Brix musts to mimic 24 °Brix musts resulted in wines with similar sensory profiles to wines made from grapes picked at a sugar content of close to 24 °Brix. This study shows that wine sensory attributes differ more when grapes are picked early in ripening rather than after 24 °Brix.